Mobile application interface design: autism spectrum disorder children / Nor Azriah Aziz - Aziz, Nor Azriah (2015)
One of the most common disabilities among Autism Spectrum Disorder (ASD) children is social interaction impairment, which particularly in recognizing facial emotion expression. As nowadays mobile application is increasingly used to support ASD children, it is important to steer the interface design of the mobile application to meet the needs of the children. Therefore, this project aims to identify the requirements of mobile application interface design for ASD children, to design the user interface and to evaluate the design for the children to learn facial emotion expression. The target users were the ASD children and teachers at Sayang's Care for Special Needs & Day Care Centre at Seksyen 7, Shah Alam. Interview with the teachers and observation on the children interaction with mobile application were conducted to gather the requirements needed. Through the analysis of the requirements, the design of the interface prototype was done after implemented the mobile application assessment and created paper-based storyboards as an early design approach. Then, the prototype underwent evaluation by the teachers and ASD children through interview and observation. The evaluation results have led to the improvement of the prototype to produce the final design of the mobile application user interface. This project will provide the appropriate user interface design for ASD children in learning facial emotion expression. In addition, it will create awareness of suitable user interface design for children with social interaction impairment.